Peran LAZISNU Dalam Meningkatkan Kemandirian Ekonomi Umat Melalui Program Gerakan Koin NU di Kabupaten Wonosobo - Muslim, Bukhori (At-Ta’awun: Jurnal Mu’amalah dan Hukum Islam, 2022)
This article discusses the role of LAZISNU in increasing the economic independence of the people in Wonosobo Regency and the strategies used by LAZISNU in increasing the economic independence of the people in Wonosobo Regency. This field research uses qualitative methods. The results of this study indicate that the role of LAZISNU in increasing the independence of the people through the NU coin program can advance the economy. This program is also the government's contribution to poverty alleviation. There are obstacles in the implementation of the coin program; Inadequate human resources, lack of management, large distribution of funds, no socialization with the community, nothing, then limited space for movement due to the Covid 19 pandemic. For LAZISNU's strategy in increasing the independence of the people through the NU coin program is to determine the target, namely the community Nahdlatul Ulama as the main target, increasing the branding of the NU coin program among the community, distributing NU coin cans, increasing human resources by forming an NU coin driving committee.